DUKUNGAN AMERIKA SERIKAT TERKAIT PENYEDIAAN MILITARY ASSISTANCE BAGI UKRAINA DALAM KONFLIK RUSIA-UKRAINA TAHUN 2014-2016 - Setiari, Ni Made; Kawitri Resen, Putu Titah; Putri, Penny Kurnia (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 2 No 1 (2022): Jurnal DIKSHI, 2022)
This research aims to describe the purpose of United States regarding the provision of military assistance to Ukraine in Russia-Ukraine conflict that expanded and escalated in 2014. The Researcher uses a qualitative method and state level of analysis with the concept of containment strategy and foreign military assistance to analyze the issue. Furthermore, the Researcher found an answer that United States's purpose in providing military assistance (non-lethal aid) was to dam up Russia’s power and its influence to Ukraine in politic-military and geocultural sphere, which has a strategic position as a corridor in entering Eurasian region with various potentials in it. The form of support provided along 2014-2016 is military equipment or weapons, military training, and military advisors. Military strength in this case is an appropriate instrument in containing Russia's influence, based on the view of military power needed by United States to defend its purposes in support Ukraine.   Keywords : Russia-Ukraine conflict, US purpose, foreign military aid, military assistance, containment strategy